Evaluation of the quality of life of patients undergoing sclerotherapy with polidocanol foam in the western region of Santa Catarina (Research, Society and Development, 2023)
The treatment of sclerotherapy with polidocanol foam has been used for patients with chronic venous insufficiency (CVI) as a less invasive form of treatment. In this study, it will be seen how it influences the clinical picture and also the quality of life of patients with CVI. The objective of the study is to evaluate patients who underwent sclerotherapy with polidocanol foam and measure the results found. The medical records of patients undergoing sclerotherapy treatment with polidocanol foam from 2016 to 2020 were evaluated using the VEINES-QOL/Sym questionnaire. A total of 71 medical records were analyzed, with an average age of 54 years, of which 80.28% were female. The average number of applications was 3.44 for each patient and the average volume was 22.75 ml of polidocanol foam per individual. This study demonstrated significant improvements in the symptoms and quality of life of patients with CVI who underwent treatment with polidocanol foam, which can be observed by the global improvement in the questionnaires answered by patients after 30 days of treatment.